Does the response to induction chemotherapy impact the timing of thoracic radiotherapy for limited‐stage small‐cell lung cancer?. Issue 5 (2nd February 2015) - Wang, Peng; Liu, Weishuai; Zhao, Lujun; Wang, Ping
Abstract: Background: To investigate whether the response to induction chemotherapy (IC) would impact the timing of thoracic radiotherapy (TRT) in limited‐stage small‐cell lung cancer (LS‐SCLC). Methods: A total of 146 patients with LS‐SCLC who had received two to six cycles of IC followed by TRT from January 2009 to December 2011 at our hospital were included in this study. Patients were divided into two groups based on the time TRT was administered: early TRT (administered after 2–3 cycles of chemotherapy) or late TRT (administered after 4–6 cycles). Overall survival (OS) and progression‐free survival (PFS) were analyzed using the Kaplan‐Meier method. Multivariate Cox regression analysis was performed to evaluate the independent factors affecting survival. Results: The median OS for patients who received early TRT and late TRT was 29.0 and 19.9 months, respectively, ( P = 0.018) and the median PFS was 18.5 and 13.8 months, respectively ( P = 0.049). In patients who achieved complete remission (CR) or partial remission (PR) after two to three cycles of IC, the median OS was 36.1 and 22.5 months in the early and late TRT subgroups, respectively ( P = 0.009); the corresponding median PFS was 20.2 and 13.8 months, respectively ( P = 0.038). In the patients who did not achieve CR or PR, no statistic difference was found in OS or PFS between the two subgroups. Conclusion: Patients who received early TRT had more favorable outcomes than those who received late TRT. Patients who achieved CR or PR after two to three cycles of IC obtained more benefit from early TRT.